A study on the protection of application software in Malaysia / Sarah Nadrah Muzaffa, Tuan Ruzuaini Tuan Lah - Muzaffa, Sarah Nadrah; Tuan Lah, Tuan Ruzuaini (2007)
Computer software is a term which can be taken to include computer programs, database, computer stored or generated document, information and also the documentation which accompanies or is associated with these items. The massive growth in the numbers of computers around and their power created an almost insatiable hunger for computer software. This newly created demand was fed by unauthorized copying of available software, often referred to as a computer piracy. The computer software industry, which had grown very quickly to meet the demand for new and better software, soon fell itself threatened by the scale of piracy. One problem for the software industry was the perceived lack of legal measures to combat unauthorized copying and piracy together with the apparent indifference of legislators to the plight of software producer.